Trust and the Demand for Personal Collateral in SME - Bank Relationships - Andrea Moro; Mike R. Lucas; Devendra Kodwani (The Journal of Entrepreneurial Finance (JEF), 2012)
Previous research on relationship lending has paid very little attention to the role of trust. Trust might be ex-pected to reduce agency costs, perceived credit risk and thus the request for personal collateral. Trustworthiness is associated with three attributes of SME owner/managers': ability, benevolence and integrity. We hypothe-sised that loan managers' assessment of the trustworthiness of owner/managers is negatively associated with the personal collateral demanded by banks. Using the quantitative and qualitative data about 457 SMEs-bank rela-tionships in North East Italy, we tested this hypothesis. The results show that trust has a minor role in reducing the request of collateral.
Keywords: G21; M13; D82; 650; Trust; Relationship lending; SMEs; Personal Collateral